Usability testing for standalone applications - Okpechi, Chidiebere Sunday (2014)
This research is focused on finding the system development mistakes that are made by system developers when they develop system interface and also how these mistakes can be avoided in order to have or create a standard that will be followed by system developers. In this research, a case study system interface “Student grading System” will be used as a test system for gathering information from the users of the system interface. The process of information gathering will be done in such a way where the users of the system will first use the system before answering a questionnaire that will be used by the researchers to get the information on how well the users of the system where able to use the system. Throughout this research, the TAM usability model will be used as a measuring tool for testing the case study system. It will also be re – designed and used as an improvement system which will stand as a solution to the mistakes found in the case study system by the users who would have used the system. Furthermore, the research will use the lucid methodology as the research methodology that will guide the researchers on the stage by stage procedures that should be followed in order for the research to be completed. The lucid methodology stands for “logical user centric interface design